Citizens' Intention to Use E-Government Services in Local Government by Integrating UTAUT, TPB, and TAM Model - Afrizal, Dedy; Luthfi, Ahmad; Bin Wallang, Muslimin; Hildawati, Hildawati; Ekareesakul, Kittipan (Journal of Local Government Issues, 2024)
In contemporary society, the widespread adoption of information and communication technologies has become integral to meeting daily needs. E-Government leverages these technologies to deliver efficient and secure services to citizens, particularly at the local government level. However, existing literature lacks comprehensive exploration into citizen preferences for utilizing e-government services, especially those offered by local governments. Addressing this gap, this study investigates citizen intentions to use e-government, focusing on the application system provided by local governments. Our research framework integrates three established models (UTAUT, TAM, and TPB) and employs empirical validation through a structured questionnaire. Data collection involved 97 respondents from diverse cities/regencies. Rigorous reliability and validity assessments were conducted on the questionnaire, with analysis performed using structural equation modeling (SEM). The findings underscore the significant influence of citizens' attitudes toward e-government, shaped by factors such as effort expectancy, facilitating conditions, and perceived risk. Furthermore, a positive and significant relationship between attitude and Intention to use revealed. This research contributes to a deeper understanding of citizen behavior towards e-government services, offering insights crucial for enhancing service delivery and citizen engagement at the local level.